Anxio-depressive disorders in a pandemic context: A comparative analysis: year 2019 versus 2020 - Andreea Roxana Droahnă; Lavinia-Alexandra Moroianu; Valeria-Anca Pietrosel; Cristina Ioana Bica; Teodor Salmen; Cecilia Curis; Emanuele Maria Merlo; Roxana Adriana Stoica; Marius Moroianu (Journal of Mind and Medical Sciences, 2023)
The outbreak of SARS-CoV-2 pandemic has resulted in increased rates of anxiety and depression worldwide. Objective. To comparatively evaluate factors associated with the psychological impact of Coronavirus disease between 2019 and the pandemic year 2020. Materials and Methods. The study was performed on a group of 3224 patients, of which 197 were hospitalized, selected from Jan 1st 2019 until 30th Dec 2020 in a tertiary care center for psychiatric disorders. Data were collected from the observation charts. Results. The incidence of anxiety disorders is higher in the age range 40-70 years with an average value of 53 years old. In 2019, a third of patients (29,45%) had alcohol-related conditions and developed anxiety-depressive disorder. In 2020, the percentage was lower (9.38%), but also the number of admitted patients significantly decreased (p<0.0001). There were not found significant differences in age, gender or environment. Hypnotic disorders were more predominant in 2019 (54.6% vs 37.5%, p=0.01), whereas in 2020 anxiety and agitation increased significantly (34.4% vs 84.38%, p=0.0001). Relapses were similarly frequent in both years, in half of the cases. Conclusions. Coronavirus pandemic lead to a decrease in both presentations and admission to hospital. Although there were not found significant differences in age or gender, more patients from urban environment were admitted, which can have several explanations. Anxiety and agitation became the main reason for hospitalization in 2020.